An alternative method based on enzymatic fat hydrolysis to quantify volatile compounds in wheat bread crumb. (1st September 2016) - Pico, Joana; Nozal, María Jesús; Gómez, Manuel; Bernal, José Luis
Highlights: An alternative method to analyse volatiles in wheat bread crumb is proposed. Lipases added to the extractant hydrolyse the fat as free fatty acids and glycerol. Extracts are easily analysed by GC/MS, free fatty acids and glycerol elute the last. The method has been fully validated with excellent analytical characteristics. Acetoin is the most abundant analyte and is responsible for crumb aroma. Abstract: An alternative method to quantify 40 volatile compounds in wheat bread crumb is proposed. It consists of a Soxhlet extraction with a mixture of dichloromethane and diethyl ether containing lipases and a subsequent concentration with Vigreux column. It is the first time that lipases are added to transform the fat into free fatty acids and glycerol, which elute at the end of the chromatogram after the analytes, avoiding problems in the chromatography due to fat residues, such as dirtiness in the injector, column clogging or overlapping peaks. The extract is most easily analysed by GC/MS, using a standard addition method to correct matrix effect. The method was fully validated, with extraction efficiencies between 70% and 100% and precision RSD lower than 15%. The method was applied to a commercial crumb, with acetoin, phenylethyl alcohol and acetic acid as highly abundant compounds, which are considered main volatiles in crumb.